Abstract Number ‐ 15: Morphological Characteristics of Ruptured and Unruptured Intracranial Aneurysms: A Systematic Literature Review and Meta‐Analysis - Sebastian Sanchez; Meredith Hickerson; Rishi R Patel; Dana Ghazaleh; Ranita Tarchand; John Pederson; Edgar A Samaniego (Stroke: Vascular and Interventional Neurology, 2023)
Introduction It is unclear what morphological features of brain aneurysms are better at predicting risk of rupture.We have performed a meta‐analysis to analyze the best morphological determinants of risk of rupture. Methods The Nested Knowledge platformwas used to search thePubMed database for studiesreporting aneurysmal size, aspect ratio (AR), size ratio (SR), ellipticity index (EI), nonsphericity index (NSI) and undulation index (UI).Effect sizes were computed as logarithmically transformed mean differences (MD) between ruptured and unruptured aneurysm. Finally, effect sizes were pooled using random‐effects and inverse‐variance weighting via restricted effects maximum likelihood estimation. Results We included 63 studies with 13,025 aneurysms: ruptured 6966 and unruptured 6059. Ruptured aneurysms were larger compared to unruptured (µ 6.1 mm, 95% CI 5.7‐6.6 vs 4.9 mm, 95% CI 4.5‐5.3 respectively, p < 0.001). There was no significant difference in size between ruptured and unruptured aneurysms in the anterior cerebral artery (ACA, p = 0.28), anterior communicating artery (ACom, p = 0.31) and basilar artety (BA, p = 0.51). AR was significantly higher in ruptured compared to unruptured aneurysms(µ 1.5,95% CI: 1.4‐1.6 vs.1.1, 95% CI: 1.1‐1.2 respectively,p < 0.001).SR was significantly higher in ruptured compared to unruptured aneurysms (µ 2.3,95% CI: 2.1‐2.5 vs. 1.6, 95% CI: 1.4‐1.8 respectively,p < 0.001).Ruptured aneurysms in the ACA and Acom had the largest mean SRs (2.5, 95% CI: 1.0‐ 6.4 and 2.6,95% CI: 2.2‐ 3.0 respectively).NSI and EI were higher in ruptured compared to unruptured aneurysms (p = 0.049 and p = 0.049, respectively). UI was similar in ruptured and unruptured aneurysms (p = 0.22). Conclusions Small aneurysms in the ACA and ACom can rupture regardless of size. SR is the best predictor of rupture status for aneurysms in these locations.SR and AR are predictors of rupture status independently of size.